VALIDACION DE ALSTROEMERIA CITRINA PHIL. (ALSTROEMERIACEAE) - Eyzaguirre Philippi, M. Teresa (Gayana Botánica, 2008)
The collection of Alstroemeria citrina Phil. in the mountains of Alicahue, located in the province of Petorca, Region of Valparaiso (November 2002), and north of Pedernales in the south of the Province of Choapa, Region of Coquimbo (November 2007), is described. The last location corresponds to the site where it was first described by Philippi in 1865. This plant had never been collected since.